2014
DOI: 10.1371/journal.pone.0085782
|View full text |Cite
|
Sign up to set email alerts
|

Ologen Implant versus Mitomycin C for Trabeculectomy: A Systematic Review and Meta-Analysis

Abstract: ObjectiveTo evaluate the application of the Ologen implant compared to mitomycin C (MMC) on the outcome of trabeculectomy and to examine the balance of risks and benefits.MethodsA systematic literature search (Pubmed, Embase, the Cochrane Library, and the Chinese Biomedicine Database) was performed. Randomized controlled trials comparing the Ologen implant with MMC in trabeculectomy were selected. The efficacy measures were the weighted mean differences (WMDs) for the intraocular pressure reduction (IOPR), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 29 publications
5
64
0
3
Order By: Relevance
“…The suboptimal performance of Ologen alone compared with MMC or Ologen with 5-FU is consistent with previous reports showing patients who receive MMC rather than Ologen have significantly lower IOP at 12 months [12][13][14]. This finding was also reinforced recently in a meta-analysis showing that patients undergoing trabeculectomy with MMC rather than Ologen experienced on average 1.94 mm Hg greater reduction in IOP, and that this difference was statistically significant [15]. Although there have been numerous studies that fail to show a difference, these studies have generally not been formally designed as non-inferiority trials and may have failed to show a difference due to lack of power [8][9][10].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The suboptimal performance of Ologen alone compared with MMC or Ologen with 5-FU is consistent with previous reports showing patients who receive MMC rather than Ologen have significantly lower IOP at 12 months [12][13][14]. This finding was also reinforced recently in a meta-analysis showing that patients undergoing trabeculectomy with MMC rather than Ologen experienced on average 1.94 mm Hg greater reduction in IOP, and that this difference was statistically significant [15]. Although there have been numerous studies that fail to show a difference, these studies have generally not been formally designed as non-inferiority trials and may have failed to show a difference due to lack of power [8][9][10].…”
Section: Discussionsupporting
confidence: 88%
“…A recent meta-analysis showed greater IOP reduction with MMC that was significant at 12 months follow-up, but noted the persistent scarcity of comparative studies with Ologen [15]. In addition, there is no study to compare the effectiveness of Ologen when it is combined with less potent but safer anti-fibrotic agent, such as 5-FU.…”
Section: Introductionmentioning
confidence: 99%
“…When metaanalysis of outcomes is appropriate, pooling across studies should increase the power and yield valuable information. Authors of a few recently published articles have addressed the effectiveness and safety of the Ex-PRESS and Ologen devices (Chen 2014;He 2014;Wang 2013a). However, a comprehensive, rigorous systematic review in this area is warranted.…”
Section: Why It Is Important To Do This Reviewmentioning
confidence: 99%
“…The results are, however, not completely consistent. Some studies [12][13][14][15][16][17][18] have found that the 2 procedures are comparable in lowering IOP whereas others have suggested that Ologen is inferior to MMC [19,20] . To the best of our knowledge, this is the first study to compare the outcomes of trabeculectomy with 5-FU versus Ologen implant in primary open-angle glaucoma.…”
Section: Discussionmentioning
confidence: 99%